Food Bioactive Compounds: Chemical Challenges and Opportunities (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In recent years, there has been a growing need for both nutritional and healthy foods with superior functional properties. In this line, bioactive compounds are economically available in different foods systems with limitations in quality and functionality.The present Special Issue is placed in this context, and aimed to provide a collection of modern chemical strategies developed with the intent of extracting, characterizing, tracing, or authenticating food bioactive compounds. Original research articles dealing with innovative techniques for the extraction (e.g., green chemistry) of bioactive compounds were welcomed. In addition, when discussing modern analytical methods, the structural characterization and identification of these active components were required. Attention was also devoted to theoretical aspects of the determination of the bioactivity and mechanisms of action of food bioactive compounds, as well as challenging properties for application as drug agents. Review articles providing an overview of the latest trends in this area of interest were also very welcomed.